1987
DOI: 10.1111/j.1547-5069.1987.tb00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Deficit: Not a Nursing Diagnosis

Abstract: This paper challenges the conceptual validity of the approved nursing diagnosis “Knowledge Deficit (specify).” The concept is examined in relation to four criteria for legitimate nursing diagnoses: appropriate conceptual focus, necessary diagnostic attributes, theoretical validity and clinical utility. Using these criteria, the author concludes that knowledge deficit is not a legitimate diagnosis and suggests that it can be dropped from the taxonomy. This would encourage clinicians to focus on patients' Proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Other commonly used diagnoses included (a) Alteration in Comfort, (b) Alteration in Cardiac Output, (c) Activity Intolerance, and (d) Ineffective Individual Coping. Jenny's (1987) model for clinical validation of nursing diagnoses proposes that diagnoses be examined in relation to four criteria for legitimacy: (a) appropriate conceptual focus, (b) necessary diagnostic attributes, (c) theoretical validity, and (d) clinical utility.…”
Section: Preliminary Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other commonly used diagnoses included (a) Alteration in Comfort, (b) Alteration in Cardiac Output, (c) Activity Intolerance, and (d) Ineffective Individual Coping. Jenny's (1987) model for clinical validation of nursing diagnoses proposes that diagnoses be examined in relation to four criteria for legitimacy: (a) appropriate conceptual focus, (b) necessary diagnostic attributes, (c) theoretical validity, and (d) clinical utility.…”
Section: Preliminary Findingsmentioning
confidence: 99%
“…According to Jenny (1987), "It is unclear what clinical finding would constitute the critical defining characteristics of a knowledge deficit when patients are not inclined to voice a lack of understanding or information" (p. 184). In reality, nurses often infer from observations that a patient lacks necessary knowledge.…”
Section: Diagnostic Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…For some authors (6)(7) , this category does not constitute a nursing diagnosis, i.e. does not constitute a human response, an alteration or a dysfunctional standard, but a related factor that can trigger other problems, such as self-care deficit, anxiety, fear, ineffective health maintenance and ineffective therapeutic regimen management.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that there are few studies about the "deficient knowledge" diagnosis, most of which were developed in the 1980s (2,6,(18)(19) . Considering the importance of identifying the patients' knowledge deficits in order to prepare hospital discharge and the establishment of an educational plan focused on individual needs, this study was started with the objective of validating the content of the defining characteristics of the "deficient knowledge" diagnosis regarding coronary disease and myocardial revascularization.…”
Section: Introductionmentioning
confidence: 99%